2012
DOI: 10.1111/j.1447-0756.2011.01738.x
|View full text |Cite
|
Sign up to set email alerts
|

Antenatally diagnosed congenital orbital teratoma in which rupture was associated with intrauterine fetal death

Abstract: We report a case of a fetus with a congenital orbital teratoma (COT), in which rupture of the tumor was associated with an intrauterine fetal demise. An ultrasound scan at 27 weeks' revealed a solid and cystic, complex mass in the orbital region with extensive vascularization suggestive of an orbital cystic teratoma. Magnetic resonance imaging (MRI) supported this diagnosis and clarified tumor localization. At 32 weeks', the patient presented with fetal demise and rupture of the mass was noted. Fetal COTs, lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
2
1
Order By: Relevance
“…Finally, in microphthalmia, ultrasound examination does not show blood flow signals in the orbit. In contrast, colour Doppler ultrasound shows a clear blood flow signal in the lesion in the present case of orbital teratoma [4]. In microphthalmia patients, the potential for visual development depends on the degree of retinal development and other ocular characteristics.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Finally, in microphthalmia, ultrasound examination does not show blood flow signals in the orbit. In contrast, colour Doppler ultrasound shows a clear blood flow signal in the lesion in the present case of orbital teratoma [4]. In microphthalmia patients, the potential for visual development depends on the degree of retinal development and other ocular characteristics.…”
Section: Discussioncontrasting
confidence: 60%
“…To our knowledge, this is the first report of a foetal orbital teratoma without proptosis. Anami et al [ 4 ] reported a large orbital teratoma with proptosis at 27 weeks and intrauterine foetal death at 32 weeks of gestation. We suspect that the absence of proptosis in our case was because the disease was in its early stage.…”
Section: Discussionmentioning
confidence: 99%
“…The third case reported a suspicion of orbital teratoma through prenatal MRI. However, the teratoma was ruptured and led to in utero fetal death [14]. The present case report is therefore the second case in which the child was born with the tumor.…”
Section: Discussionmentioning
confidence: 70%